ADAPTASI VISUAL DALAM TRANSFORMASI FUNGSI BANGUNAN URBAN CAFE ESTETIK DI KAJOETANGAN MALANG: ADAPTASI VISUAL DALAM TRANSFORMASI FUNGSI BANGUNAN URBAN CAFE ESTETIK DI KAJOETANGAN MALANG - andika agung sutrisno; Andhika Putra Herwanto; Dhara Alim Cendikia (Universitas Telkom, 2025)
Abstract: The Kajoetangan area in Malang has undergone a significant transformation since being designated a cultural tourism destination, marked by the emergence of classic-style cafes that blend historical value with modernity. This study is based on the theoretical hypothesis that the appeal of Hamur Mbah Ndut Café does not stem solely from nostalgic decor, but rather from a strategy of visual identity adaptation. It is hypothesized that the success of Hamur Mbah Ndut Café lies in its ability to preserve the original residential building (through its facade and structure), which is then integrated with new decorative elements.The aim of the research is to explore how visual elements such as facades, interiors, and instagramable spatial layout contribute to visitor experience and city branding. The approach used is phenomenology, with data collection techniques through in-depth interviews, field observations, and thematic analysis. The results of the study show that Café Hamur Mbah Ndut has managed to build a strong visual appeal and revive cultural values through authentic and adaptive design. Visual aesthetics not only increase visitor comfort and loyalty, but also encourage digital promotion through social media. However, increased visits also pose challenges, such as overcrowding, environmental degradation, and social pressures. Therefore, visitor mitigation strategies such as the contribution of IDR 5,000 entrance tickets for environmental management are an important part of sustainability efforts. This study concludes that the synergy between visual aesthetics, local identity, and sustainable management makes the Kajoetangan area develop as an inclusive, adaptive, and characterful cultural tourism destination. Keywords: visual aesthetics; heritage; café; cultural tourism; visitor mitigation